Cefixime removal from wastewater by adsorption on activated carbon derived from broad bean peels using response surface methodology with Box–Behnken design - Sabbar, Huda Adil (Al-Khwarizmi Engineering Journal, 2026)
In this study, cefixime (CFX) was removed from aqueous solutions by using activated carbon (AC) made from broad bean peels (BBPs). To evaluate the adsorbent performance, a conventional experimental approach (one factor at a time) was applied to clarify the impact of the most influential variables (i.e., pH, contact time, and adsorbent dosage) and identify the maximum adsorption capacity. The optimization approach of response surface methodology with a Box–Behnken design (BBD) was employed to investigate the synergistic influences of the three independent variables and determine the optimum experimental conditions. Removal efficiency (%) was evaluated at different pH (2–10), contact time (10–150 min), and adsorbent dosage (0.1–2.5 g L-1). Results revealed that the measurements adequately fitted the Langmuir isotherm, with a maximum monolayer adsorption capacity (qm) of 17.5 mg/g. Moreover, based on the optimization approach, 95% removal efficiency was reached at optimum values of 6, 100 min, and 2.16 for pH, contact time, and adsorbent dosage, respectively. The BET surface area was determined to be 375 m²/g, and the total pore volume was 0.204 m³/g. For multilayer sorption, the isotherm and kinetic models were suggested, followed by exothermic an physical adsorption mechanism. The findings of this study indicate that AC prepared from BBPs can be used as an adsorbent to remove CFX from aqueous solutions.